People power as a form of citizen participation - Bautista, Victoria A. (Philippine Journal of Public Administration, 1986)
People power is an alternative to the regular institutional channels that have failed. It involves the people's expression of their stand and calling for a resolution of pressing national issues. People power is a form of citizen's participation that is central to the theory of participatory democracy in political science and public administration. A major problem confronting the government is its failure to effectively employ participatory strategy in the formulation and implementation of its programs and projects. People power was the recourse when formal legal channels for participation broke down. It is within this context that people power is considered a boon primarily because of its meaningful capability to contribute to the achievement of the popular will. People power as a form of meaningful citizen participation should extend itself to the implementation of development programs and projects.